Pengaruh Beban Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Di PT. Orientama Makmur Abadi - Andre Christian; Ignatius Ario Sumbogo (Research and Community Service UNIVERSITAS KALBIS, 2022)
This study aims to determine whether there is an influence between workload and work discipline on employee performance at PT. Orientama Prosperous Eternal. The population in this study were employees of PT. Orientama Prosperous Eternal. Sampling technique using saturated samples. The analytical method used in this research is using multiple linear regression analysis. This study uses a quantitative approach through distributing questionnaires to 100 employees of PT. Orientama Prosperous Eternal. The results of the hypothesis test (t test) show that the workload variable has a significant effect on the employee performance variable. This is indicated by the t arithmetic value of 3.375 > t table 1.984 which is greater than t table. Likewise, work discipline has a significant effect on employee performance variables with t count 4.855 > t table 1.984 which is greater than t table. The conclusion of this study is that workload and work discipline have a significant effect on employee performance. employee performance, Oeriantama, workload, work discipline